Effectiveness and cost-effectiveness of neuromuscular exercise and back care counseling in female healthcare workers with recurrent non-specific low back pain: a blinded four-arm randomized controlled trial - Jaana Helena Suni; Päivi Kolu; Kari Tokola; Jani Raitanen; Marjo Rinne; Annika Taulaniemi; Jari Parkkari; Markku Kankaanpää (BMC, 2018)
Abstract Background Registered healthcare workers worldwide have a high prevalence of work-related musculoskeletal disorders, particularly of the back. Multidisciplinary interventions among these workers have improved fear avoidance beliefs, but not low back pain (LBP) and related sickness absences, cost-effectiveness studies are scarce. Our purpose was to investigate the effectiveness and cost-effectiveness of three intervention-arms (combined neuromuscular exercise and back care counselling or either alone) compared with non-treatment. Methods We randomly assigned female healthcare workers with recurrent non-specific LBP to one of four study-arms: Combined neuromuscular exercise and back care counseling; Exercise; Counseling; and no intervention Control. We assessed the effectiveness of the interventions on intensity of LBP, pain interfering with work and fear avoidance beliefs against the Control, and calculated the incremental cost-effectiveness ratios for sickness absence and QALY. Results We conducted three sub-studies in consecutive years of 2011, 2012, and 2013 to reach an adequate sample size. All together 219 women were randomized within each sub-study, of whom 74 and 68% had adequate questionnaire data at 6 and 12 months, respectively. No adverse events occurred. Compliance rates varied between intervention-arms. After 12 months, the Combined-arm showed reduced intensity of LBP (p = 0.006; effect size 0.70, confidence interval 0.23 to 1.17) and pain interfering with work (p = 0.011) compared with the Control-arm. Work-related fear of pain was reduced in both the Combined- (p = 0.003) and Exercise-arm (p = 0.002). Physical activity-related fear was reduced only in the Exercise-arm (p = 0.008). During the study period (0-12 months) mean total costs were lowest in the Combined-arm (€476 vs. €1062-€1992, p < 0.001) as were the mean number of sickness absence days (0.15 vs. 2.29-4.17, p = 0.025). None of the intervention-arms was cost-effective for sickness absence. There was 85% probability of exercise-arm being cost-effective if willing to pay €3550 for QALY gained. Conclusions Exercise once a week for 6 months combined with five sessions of back care counseling after working hours in real-life settings effectively reduced the intensity of LBP, work interference due to LBP, and fear of pain, but was not cost-effective. Trial registration ClinicalTrials.gov, NCT01465698 November 7, 2011 (prospective).